165 Rates of SGLT2 Inhibitor Use in Patients With Diabetes and Heart Failure in the Southeastern United States. (April 2022) - Gangavelli, Apoorva; Liu, Zihao; Wang, Jeffrey; Okoh, Alexis; Patel, Shivani; Morris, Alanna A.
Abstract : OBJECTIVES/GOALS: Clinical trials of SGLT2 inhibitors in patients with heart failure (HF) have confirmed a reduction in hospitalization and death. Adoption of novel therapeutics has been slower in Black and female patients. We investigated utilization of SGLT2 inhibitor in patients with HF and type 2 diabetes and if there were utilization differences by race or gender. METHODS/STUDY POPULATION: We created a retrospective cohort of outpatients with HF at Emory Healthcare from 2015 to 2020. Additional inclusion criteria included presence of heart failure and a diagnosis of T2D. SGLT2 inhibitor use was identified by a presence of SGLT2 inhibitor prescription at the time of the clinic visit. We estimated differences in prescription of SGLT2 inhibitors by race and gender using Chi-square analysis. RESULTS/ANTICIPATED RESULTS: The cohort included 5829 patients, age 69.47 years Â± 13.44, 47.67 % female, 54.62% Black. Overall prescription of SGLT2 inhibitors was low but increased over time (1.4% in 2015 to 5.6% in 2020; p<0.0001). On average, SGLT2 inhibitor use increased annually by 44.77%. From 2015 to 2020, fewer female than male patients were on an SGLT2 inhibitor (1.94% vs. 2.73%, p=0.0033). A similar percentage of Black and non-Black patients were on an SGLT2 inhibitor (2.13% vs. 2.64%, p=0.0591). DISCUSSION/SIGNIFICANCE: Prescription rates of SGLT2 inhibitors remain low in patients with T2D and HF, especially for female patients, despite evidence of their benefit on hospitalizations and mortality. Implementing use of SGLT2 inhibitors in this population represent an opportunity to improve cardiovascular outcomes.